Chlorine determination in medicinal plants by potentiometry with ion-selective electrode after microwave-induced combustion - Mariele Samuel Nascimento; Gabriel Toneto Druzian; Rochele Sogari Picoloto; Paola Azevedo Mello; Erico M. M. Flores (Drug Analytical Research, 2021)
A method based on microwave-induced combustion (MIC) was applied for medicinal plants digestion allowing further chlorine determination by potentiometry using ion-selective electrode (ISE). Sample masses ranging from 500 to 1000 mg were evaluated for MIC digestion. Water and 10, 25, 50, and 100 mmol/L NH4OH were investigated as absorbing solutions. The accuracy of the proposed method was evaluated by using certified reference materials (CRMs), by recovery tests (500 µg/g), and also by comparison with the results obtained by inductively coupled plasma optical emission spectrometry (ICP-OES) after microwave-assisted alkaline extraction (MAE). Using water or NH4OH solutions (10 to 100 mmol/L), recoveries close to 100% and relative standard deviation lower than 5% were obtained. Results were in agreement with CRMs values (better than 95%) and also with those values obtained by using the MAE method. The main advantage of the proposed method was the complete combustion of high sample mass (1000 mg) resulting in low quantification limit (12.5 µg/g) and chlorine determination at low concentration by ISE. Another advantage of the proposed method was the high chlorine stability in digests (up to 30 days of storage) even using water as absorbing solution, which is in agreement with green analytical chemistry recommendations. Finally, the proposed MIC method was applied for commercial medicinal plants and the chlorine concentration was in the range of 59.4 ± 1.4 to 2038 ± 70 µg/g. The proposed MIC method was considered suitable for quality control for chlorine determination in medicinal plants.